P-358 Effect of endometrial thickness on biochemical pregnancy rate: an analysis of 1534 frozen euploid embryo transfers. (30th June 2022) - Mattar, S; Liñán, A; Shanker, U; Ruiz, F; Elkhatib, I; Lawrenz, B; Fatemi, H.M
Abstract: Study question: Can a thick endometrial lining measured prior to embryo transfer be considered a protective factor against Biochemical Pregnancy (BP)? Summary answer: The risk of BP is independent of Endometrial Thickness (EMT), but rather dependent of the type of endometrial preparation and parity. What is known already: Higher EMT prior to embryo transfer is associated with better clinical outcomes in general, like higher implantation and livebirth, and lower miscarriage rates. But up to our knowledge, no studies evaluated the effect of EMT on BP per say. Study design, size, duration: This is a two-center retrospective observational study including a total of 1534 euploid Frozen Embryo Transfer (FET) cycles between March 2017 and March 2020 at ART Fertility Clinics Muscat, Oman and Abu Dhabi, UAE. BP is defined as blood beta-hCG >15 mIU/ml on day 12 post FET, that is progressively decreasing, with no evidence of gestational sac on ultrasound. Participants/materials, setting, methods: The study group consisted of 112 cases of BP, while the control group consisted of the remaining 1422 FET's that led to different clinical outcomes. EMT was measured by transvaginal ultrasound on the day of progesterone rise (±1 day); that rise was either spontaneous in Natural Cycles (NC), or iatrogenic in Hormone Replacement Therapy (HRT) cycles. Euploidy status of the embryos was assessed by NGS analysis of trophectoderm biopsies. Bivariate and multivariate analyses were conducted. Main results and the role of chance: There was no difference in mean EMT between the study and the control groups (7.55 vs. 7.68 mm, p = 0.154). Looking at the association of different variables with the rate of BP, there was no effect of age, BMI, AMH, number of embryos transferred, degree of blastocyst expansion, inner cell mass or trophectoderm grade, day of biopsy, nor presence of blood or mucus on the transfer catheter. However, patients on HRT cycles had significantly higher rates of BP compared to NC (8.42% vs. 4.99%, p = 0.015). Also, those with a previous livebirth had higher rates of BP compared to nulliparous women (8.7% vs. 5.39%, p = 0.014). The distribution of BP showed that 54.5% occurred with EMT <7.5 mm, 34.8% with EMT 7.5-9 mm, and 10.7% with EMT >9 mm. These represents respectively 8.16%, 6.68%, and 5.94% of the total sample. This decreasing trend of BP with increasing EMT didn't reach statistical significance (p = 0.429). Univariate analysis comparing the risk of BP in FET's done with lower and higher EMT to those performed at 7.5-9 mm yielded similar conclusion: OR = 1.24 [0.82-1.88] for <7.5 mm, and OR = 0.88 [0.45-1.72] for >9 mm. Controlling for different confounders, HRT cycles and multiparity remained as independent risk factors for BP. Limitations, reasons for caution: Inter-observer variability in EMT measurement and the transfer technique, the retrospective nature of the study, and the lack of data on the mode of delivery of parous women could all have interfered with the conclusion. Wider implications of the findings: The reduced adverse clinical outcomes with NC shed light on the role of the corpus luteum in the early phases of implantation, and some potential secreted mediators other than progesterone. Besides, the effect of previous deliveries on the endometrium and its receptivity needs further investigation. Trial registration number: not applicable